Climate effects on temporal and spatial dynamics of phytoplankton and zooplankton in the Barents Sea - Dalpadado, Padmini; Arrigo, Kevin R.; van Dijken, Gert L.; Skjoldal, Hein Rune; Bagøien, Espen; Dolgov, Andrey V.; Prokopchuk, Irina P.; Sperfeld, Erik (Progress in oceanography, 2020)
•The Barents Sea is undergoing unprecedented changes in temperature and sea ice cover.•Less sea ice leads to more open water and longer growing seasons for phytoplankton.•Strong increase in net primary production (NPP) estimates during the last 20 years.•Higher NPP may have caused stable mesozooplankton biomass in recent years.•Weakening of negative relationship between capelin and zooplankton in recent years. Temporal and spatial dynamics of phytoplankton and zooplankton in the Barents Sea have been investigated during the last three decades using remote sensing and in situ observations. Satellite-derived sea surface temperatures increased in the period 1998–2017 by 1.0 °C as an average for the Barents Sea. We found significant positive relationships between ice-free conditions (open water area and duration) and satellite-based net primary production (NPP). The estimated annual NPP for the Barents Sea more than doubled over the 1998–2017 period, from around 40 to over 100 Tg C. The strong increase in NPP is the result of reduction of sea ice, extending both the area and period available for phytoplankton production. In areas where ice extent has decreased, satellite-derived chlorophyll a shows that the timing of the peak spring phytoplankton bloom has advanced by over a month. Our results reveal that phytoplankton dynamics in the ecosystem have been changing rapidly and that this change is driven mainly by bottom-up climatic processes. Autumn mesozooplankton biomass showed strong interannual variability in the 1990s, displaying an inverse relationship with capelin biomass, the most abundant planktivorous fish. In some regions, e.g. Central Bank, capelin biomass explained up to 50% of the mesozooplankton variability during 1989–2017. Though capelin biomass has varied considerably, mesozooplankton biomass has remained rather stable since the mid-2000s (6–8 g dry wt. m−2), resulting in a weakening of the negative relationship between capelin and mesozooplankton biomass in recent years. The stable zooplankton biomass indicates favorable conditions (prolonged/increased NPP) for mesozooplankton production, partly counteracting high predation levels. Overall, we observed trends in phytoplankton phenology that were strongly associated with changes in sea ice cover driven by fluctuations in temperature regime, a trend that may intensify should the ecosystem become even warmer due to climate change. Further reductions of sea ice and associated ice algae is expected to have adverse effects on sympagic fauna and ice dependent species in the Arctic food web. The ice-free conditions may promote further Atlantification (or borealization) of plankton and fish communities in the Barents Sea.